Pediatric eosinophilic esophagitis: a Belgian single-center retrospective analysis reveals real-life difficulties in diagnosis and treatment - Dominicus, Toon; Nuyttens, Lisa; Hoffman, Ilse; Bullens, Dominique M. A. (Frontiers in Allergy, 2024)
IntroductionEosinophilic esophagitis (EoE) is a chronic immune-mediated disorder characterized by eosinophilic infiltration of the esophageal mucosa.MethodsThis study aimed to provide insights into the clinical characteristics, diagnostic evaluation, treatment modalities, and outcomes of EoE in a pediatric population through a retrospective analysis of 79 patients followed in a single tertiary referral center between 2014 and 2020.ResultsAs expected, a higher male prevalence was observed. Median age at diagnosis was 8.9 years, aligning with the typical presentation in childhood, emphasizing the need for early recognition. Clinical presentation varied, with vomiting, dysphagia, and abdominal pain being the most frequently reported symptoms. IgE-sensitization, food allergy and atopy were highly prevalent, with cow's milk, wheat, egg, soy, and peanuts being the most common allergens. Endoscopy results mostly revealed macroscopic abnormalities with linear furrows and microabscesses/white plaques being the most common features although a significant proportion of initial endoscopies (14/79) showed no macroscopic abnormalities, highlighting the importance of esophageal biopsies. Proton pump inhibitors (PPIs) were commonly used as a first-line treatment, with most patients receiving PPI therapy. Other treatment modalities, such as oral budesonide and exclusion diets either single or in combination, were also used. Remission was achieved in 69/79 or 87% patients, with different treatment regimens contributing to successful outcomes but subject to relapse upon time.DiscussionThis study provides valuable insights into the clinical characteristics, diagnostic evaluation, treatment modalities, and outcomes of EoE in the pediatric population. It underscores the importance of early recognition, accurate diagnosis, and regular follow-up to effectively manage this chronic immune-mediated disorder but also demonstrates its complexity in real-life clinical setting.